Dynamic insulation systems to control airborne transmission of viruses in classrooms: a review of ‘Airhouse’ concept - Mohd-Sahabuddin, Mohd Firrdhaus; Dahlan, Ammar Sadik; Mohamad Jamil, Azli; Muhammad Sukki, Firdaus (Penerbit Universiti Kebangsaan Malaysia, 2022)
The discovery of the Covid-19 virus in China at the end of 2019 has drastically altered the global landscape. The virus, which has now become a pandemic, has wrought devastation on the world, infecting over 500 million people and killing over 6 million. The virus’s mutation into a few variations, however, has enabled the world’s alarming situation to continue until now. Airborne particles and viruses including the new Covid-19 variant – Omricon, is not only extremely contagious but also can be transferred by airborne transmission, putting vulnerable people like children at risk, particularly in classrooms. Amongst the strategies to control airborne transmission of viruses and to improve indoor thermal and air quality is using ventilation strategies – such as dynamic insulation. Thus, this paper will review at how dynamic insulation systems in conventional farming and residential buildings, cleanrooms and other controlled environments work to reduce airborne viruses and particles in a room. An innovative “Airhouse” concept that combines with activated carbon has been researched and investigated with regard to the dynamic insulation systems.This system has a high potential to reduce the air temperature, humidity, and airborne viruses including Covid-19 whilst maintaining a steady airflow rate in a normal room. Therefore, it has a great deal of potential to decrease or eliminate concerns about the transmission of airborne viruses and adapt ventilation systems to new pandemic threats.